Contact metamorphism of coals in the Southern Piceance Basin, USA: Volatile matter generation, pyrolytic carbon accumulation, and δ13C trends - Susan M. Rimmer; Lois E. Yoksoulian; Darren R. Gröcke (Evolving Earth)
Four transects of coal were studied to determine petrographic, geochemical, and δ13C changes due to contact with thin sills. Approaching the sills, vitrinite and coke reflectance increases from ∼0.75% to ∼7%, while volatile matter (VM) and H/C decrease. Despite extensive VM loss, the coals do not follow normal burial maturation pathways. Alteration above the sills exceeds that below, and the width of the contact aureole is large compared to that of the sills. This may suggest prolonged magma transport within the sills. Additionally, multiple fractures contain coke, pyrolytic carbon, and minerals, which suggests migration of fluidized coal, VM, and hot fluids. Incipient mosaic and anisotropic coke structures (fine-grained circular mosaic, with minor medium-grained circular mosaic) are observed within the aureole, consistent with intrusion of a high volatile bituminous coal. Devolatilization vacuoles, more abundant in altered collodetrinite than collotelinite, increase in number and size approaching the sills. Pyrolytic carbon occurs as fracture fills, spherulites, and botryoidal aggregates; spherulitic forms are more abundant at higher maturation levels. δ13C of the altered coal/coke varies only minimally from that of the unaltered coal and overall trends are ambiguous. Factors affecting δ13C may include maceral composition, rank at the time of intrusion, extent of alteration, size of the carbon reservoir, redeposition of pyrolytic carbon, and openness of the system. It is possible that the rapid heating and high temperatures associated with contact metamorphism limit carbon isotopic fractionation. In turn, this may imply that the intrusion of coal results in minimal liberation of isotopically light CH4.